TRPV4 disrupts mitochondrial transport and causes axonal degeneration via a CaMKII-dependent elevation of intracellular Ca2+ - Brian M. Woolums (Nature Portfolio, 2020)
Mutations in the TRPV4 channel cause inherited neurodegeneration syndromes, but the molecular mechanisms are unknown. Here the authors reveal that TRPV4 activation causes dose-dependent, CaMKII-mediated neuronal dysfunction and axonal degeneration via disruption of mitochondrial axonal transport.